1991
DOI: 10.1177/105960119101600105
|View full text |Cite
|
Sign up to set email alerts
|

Women's and Men's Expectations About the Effects of New Technology at Work

Abstract: This article compares the views of men and women employed in hourly production jobs regarding the effects of an innovation on their working conditions, their organization, and the rewards they receive. Gender differences are found on an array of expectations likely to influence the innovation process, including knowledge of and general attitude toward new technology, job security, safety, learning opportunities, training and technical assistance, and rewards. Gender differences persist when education, age, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The early studies show a significant gap existing between user observations of a newly implemented IS and user prior expectations (Argote et al, 1983), and suggest that the efforts of instilling realistic expectations in users of a proposed IS may likely lead to better satisfaction with the resultant IS (Ginzberg, 1981). Related studies also concur that user expectation reflects the understandings by users of business issues that necessitate a proposed IS, the resultant organizational changes, and the consequences relevant to individuals (Ginzberg, 1981;Hackett et al, 1991). In comparison to the constructs-user involvement, user attitude, and even user expectation-all of which are aimed to position users properly only during ISD, only the organizational change perspective, though too general, directs our consideration of user factors around, rather than just during, ISD, and thus, in our view, points to a promising direction in search of winning approaches to ISD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The early studies show a significant gap existing between user observations of a newly implemented IS and user prior expectations (Argote et al, 1983), and suggest that the efforts of instilling realistic expectations in users of a proposed IS may likely lead to better satisfaction with the resultant IS (Ginzberg, 1981). Related studies also concur that user expectation reflects the understandings by users of business issues that necessitate a proposed IS, the resultant organizational changes, and the consequences relevant to individuals (Ginzberg, 1981;Hackett et al, 1991). In comparison to the constructs-user involvement, user attitude, and even user expectation-all of which are aimed to position users properly only during ISD, only the organizational change perspective, though too general, directs our consideration of user factors around, rather than just during, ISD, and thus, in our view, points to a promising direction in search of winning approaches to ISD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is important to find whether perception differences exist within different age categories. Gender is selected because gender differences have been documented in the literature as affecting perception (Hackett, Mirvis and Sales, 1991). As a result, it is imperative to find whether gender differences exist between male and female respondents.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Pope-Davis and Twing (1991) examined attitudes toward computer technology in university students and found no gender differences. Hackett, Mirvis, and Sales (1991), however, in a study of 654 people employed in hourly production jobs, found women to be generally more pessimistic about the effects of new technology in the workplace than men. It may well be that women are reasonably skeptical of technologies that may change their lives in undesirable ways, perhaps by eliminating or de-personalizing work, and by making pregnancy and birth subject to unwanted medical control.…”
Section: Gendermentioning
confidence: 99%